THE ATTITUDE SCALE TOWARDS DISTANCE NURSING EDUCATION (astDNE) - (:unkn) unknown (ANADOLU UNIV, 2015)
In this study, a measurement is seen as an instrument to measure the attitudes of the nurses towards the distance nursing education was developed. The study population consist of nurses who working in two hospitals of the ministry of health and two special hospitals in Istanbul. The sample of the study consisted of 194 nurses who agreed to participate in this study. The scale total cronbach alpha coefficient was found .94, test-retest reliability coefficient .89. The correlations of each item with total point were between .49 and .69. In factor analysis done with varimax rotation for construct validity, whose eigenvalue is over 1, explaining 65.02 % of total variability, 5 factors consisting of 25 items was obtained the scale. These factors are called Interaction, Learning Styles, Support Services, Interaction Tools and Content Presentation. Consequently, findings show that The Attitude Scale towards Distance Nursing Education (astDNE) is a valid and reliable instrument.
Keywords: The attitude scale; distance nursing education; astDNE